Visceral Uric Gout in Muscovy Duck (Cairina moschata) - Dall'Agnol Krause, Catherine; Orrigo Prates, Ingrid Tayná; da Silva Vargas, Andressa; Barruffe Fiscuk, Eduarda; Luzza Favreto, Isadora; Froner Argenta, Fernando; Zafalon da Silva, Bruna; Barreto Coelho, Ana Carolina (Acta Scientiae Veterinariae, 2023)
Background: Gout, a metabolic disease affecting multiple species, is frequent in birds which are uricotelic animals. It is primarily caused by hyperuricemia originating from birds’ renal disorders with subsequent deposition of urate crystals into tissue. The location of the crystals determines the type of disease. Joint disease occurs with deposition inside and around joints, joint capsules, and tandine hems, while visceral disease occurs when the serous surface of visceral organs (mainly pericardium, liver, kidneys, air sacs, peritoneum, and spleen) are affected. This report describes a case of visceral uric gout in a Muscovy duck, which is rare. Case: An adult, male, Muscovy duck (Cairina moschata), kept under human care in a zoo, was referred to a veterinary clinic. The animal presented suddenly with prostration, ataxia, and anorexia, and died the following day. The body was sent to the Pathology Sector of Ritter dos Reis University Center (UniRitter) for a necropsy. During the necropsy, it was observed that white membranes, presenting a “chalk dust” appearance, were deposited under the serous layer of organs including the liver, kidneys, and pericardium. Following the necropsy and macroscopic evaluations, fragments of multiple organs were fixed in 10% formalin and processed routinely with hematoxylin and eosin (HE) staining for histopathological evaluation in an analysis laboratory in Porto Alegre city. A deposition of amorphous eosinophilic material was identified in the intestine, liver (serous), kidneys, lungs, and heart (epicardium) with findings of serositis, nephritis, and fibrinous epicarditis. The liver parenchyma and lungs had areas of congestion. There was both moderate and intense hepatocellular degeneration as well as degeneration in the renal tubular cells. These macro and microscopic changes were compatible with urate crystal deposition which represents visceral uric gout. Discussion: As opposed to free-living birds, birds in captivity have easy access to food and are sedentary. These factors, together with inadequate food management, make nutritional disorders the main predisposing cause of uric gout in these animals. Since it was not possible to determine the causative factors of this individual animal’s disease due to the absence of examinations while alive, a nutritional origin of this animal’s demise was considered. According to prior reports, an important cause of avian disease can be attributed directly or indirectly to kidney dysfunction. In addition to a deposition of amorphous material in the renal cortex, this Muscovy duck had areas of tubular cell degeneration and proliferation of fibrous connective tissue. However, it was not possible to establish a cause and effect relationship between the renal damage and the uric gout. Despite being common in birds under human care, the disease still is challenging for veterinarians, since the diagnosis is often late and treatment is often ineffective. The absence of documentation of this disease in the Muscovy duck contributes to the difficulty in establishing predisposing factors and a distinct disease etiology. This highlights the importance of the present report and the need for new studies. To the best of our knowledge, this is the first report of visceral uric gout in a Muscovy duck (Cairina moschata). This highlights the importance of necroscopic examinations and the impact they can have in the clinical arena, especially in wild animals. Keywords: metabolic disorder, necropsy, pathology, renal disease, wildlife. Título: Gota úrica visceral em pato-do-mato (Cairina moschata) Descritores: animais silvestres, distúrbio metabólico, doença renal, necropsia, patologia.